Autologous Long Head of Biceps Tendon With High-Strength Suture for Reconstruction of Coracoclavicular Ligament - Huazheng Qu, M.D.; Hepeng Yu, M.D.; Ji Li, M.D.; Qiang Zhang, M.D. (Arthroscopy Techniques, 2025)
Acromioclavicular joint (ACJ) dislocations are common shoulder injuries. The most common causes of ACJ dislocations may also lead to SLAP lesions, which are the most common types of labral tears associated with ACJ dislocations. Tenotomy of the long head of the biceps tendon (LHBT) is one viable alternative for proximal biceps tendon pathology or SLAP tears, yielding high patient satisfaction. We describe a hybrid technique of autologous LHBT combined with FiberTape (Arthrex, Naples, FL) in a venae comitantes fashion in which a parallel figure-of-8 conjoint stabilizer is constructed for coracoclavicular ligament reconstruction to manage chronic ACJ dislocation concomitant with proximal biceps tendon pathology or SLAP lesions. The LHBT harvest procedure is entirely performed under arthroscopy and completely accomplished at the target location. In view of the high prevalence of glenohumeral pathologies concomitant with ACJ dislocation, as well as the high correlation between ACJ dislocation grades and the prevalence of SLAP tears, there are reasons to believe that the LHBT should be put to extensive use as a graft.